Perancangan Sistem Informasi Penjualan Sembako pada Toko Misman - Asih Della Saftini (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The purpose of this research is to design a basic food sales information system at Misman Store to assist the performance of Store employees in processing data and selling basic necessities which still use a manual recording system in managing stocks and transactions in the store, which causes inefficiencies in monitoring inventory of goods. Research using qualitative methods with data collection techniques through observation, interviews, and literature studies. The results of the study, among others, make it easier for employees at misman shops to complete the main tasks of selling goods such as data management to be easier, more efficient, and effective with this system. sales and sales transaction reports. The designed web-based information system has several main features such as system login, dashboard, item category management, inventory management, and transaction recording and reporting. This system is designed to improve the efficiency of store operations and facilitate the management of goods data and sales transactions.